Dynamic Compression Behavior and a Damage Constitutive Model of Steel Fibre Reinforced Self-Compacting Concrete - Liang Bian (Hindawi Limited, 2021)
The dynamic behavior of steel fibre reinforced self-compacting concrete (SFRSCC) was investigated by using a split Hopkinson pressure bar (SHPB). SFRSCC specimens with two strength classes of about 40 MPa and 60 MPa were prepared. Different steel fibre volume fractions were used varying from 0.5% to 2.0%. The tested strain rate ranged from about 50 to 240 s−1. Signiﬁcant rate dependence was observed, and dynamic increase factor (DIF) was used to quantify the rate sensitivity. The results showed that both the matrix strength and fibre content had effect on the strain rate sensitivity of SFRSCC. A DIF formula was proposed for describing the dynamic strength of SFRSCC at high strain rates, and a dynamic damage constitutive model was derived to describe the stress-strain relationship of SFRSCC. The parameters in the model were determined by fitting the experimental data. Good consistency between theoretical curves and experimental data was obtained.